2018
DOI: 10.1016/j.coi.2018.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Control of B-1a cell development by instructive BCR signaling

Abstract: B-1a cells remain one of the most enigmatic lymphocyte subsets. In this review, we discuss recent advances in our understanding of the development of these cells and their regulation by the transcription factors Bhlhe41 and Arid3a as well as by the RNA-binding protein Lin28b. A large body of literature supports an instructive role of BCR signaling in B-1a cell development and lineage commitment, which is initiated only after signaling from an autoreactive BCR. While both fetal and adult hematopoiesis can gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 70 publications
1
21
0
Order By: Relevance
“…Immune cells are generated by hematopoietic stem and precursor cells (HSPCs). In the mouse model, evidence has been obtained for the developmentally ordered appearance (or “layered development”) of distinct HSPCs that give rise to distinct immune cell lineages at different stages of development, including the generation of innate lymphocytes such as dendritic epidermal T cells and B1 lymphocytes (Ikuta et al, 1990; Havran and Allison, 1990; Yuan et al, 2012; Ginhoux and Jung, 2014; Beaudin et al, 2016; Ramond et al, 2014; Gentek et al, 2018; Kreslavsky et al, 2018; Smith et al, 2018). However, other studies indicate that the available niche at the time of development is more important (van de Laar et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Immune cells are generated by hematopoietic stem and precursor cells (HSPCs). In the mouse model, evidence has been obtained for the developmentally ordered appearance (or “layered development”) of distinct HSPCs that give rise to distinct immune cell lineages at different stages of development, including the generation of innate lymphocytes such as dendritic epidermal T cells and B1 lymphocytes (Ikuta et al, 1990; Havran and Allison, 1990; Yuan et al, 2012; Ginhoux and Jung, 2014; Beaudin et al, 2016; Ramond et al, 2014; Gentek et al, 2018; Kreslavsky et al, 2018; Smith et al, 2018). However, other studies indicate that the available niche at the time of development is more important (van de Laar et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…B-1 cells display a primitive, innate-like functionality and produce natural antibodies, independent of T cell help (Hayakawa et al, 1983). In humans, the existence of a B-1 cell counterpart is debated (Baumgarth, 2011;Caligaris-Cappio et al, 1982;Ehrhardt et al, 2005;Griffin et al, 2011;Kreslavsky et al, 2018;Kruetzmann et al, 2003;Perez-Andres et al, 2011;Rakhmanov et al, 2009;Reynaud and Weill, 2012;Wardemann et al, 2002;Weller et al, 2008), CD5 expression is not confined to a fetal B cell lineage (DiLillo et al, 2010;Seifert et al, 2012;Sims et al, 2005;Wortis et al, 1995) and human neonatal B cells share only few of the defects observed in mice (Adkins et al, 2004;Tasker and Marshall-Clarke, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In the case of B1 cells, this possibly even occurs prior to hematopoietic stem cell differentiation (7)(8)(9)(10). As recently reviewed in detail, definitive evidence for the lineage model is still lacking, with both putative BCR-negative B1 progenitors and exclusive progenitor commitment to B2 differentiation being controversial (11,12). In the "selection model," B cell progenitors are instructed by BCR specificity to differentiate into B1 cells, depending on BCR-mediated recognition of common bacterial and certain self antigens (2,13).…”
mentioning
confidence: 99%